Crips - Crash Recognition & Injury Prevention in alpine ski racing - Huber, A.; Spitzenpfeil, P.; Waibel, K.; Debus, D.; Fozzy Moritz, E. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Heavy injuries due to crashes and/ or extraordinary strain cause either long breaks in training and competition or sometimes the end of the career. On the other hand crashes are part of that sport. The development of a sensor-based system solution for alpine skiing, that detects threatening falls on the earliest possible moment, should give the opportunity to initiale appropriate prevention or minimization of the consequences. Last season we started first measurements on German elite skiers in training and, by authority of the FIS, with forerunners at the downhill men and women race at the FIS-WC final 2009/ 2010 in Garmisch-Partenkirchen